Corporate social responsibility in junior and mid-tier resources companies operating in developing nations – beyond the public relations offensive. (December 2016) - Lyons, Margaret; Bartlett, Jennifer; McDonald, Paula
Abstract: This study explores how junior and mid-tier resources companies operating in the world's most impoverished countries understand and practice corporate social responsibility (CSR), and its relationship to their assumed social licence to operate (SLO). The study drew on emergent research that finds smaller companies, which are less subject to scrutiny by external stakeholders such as NGOs, media and investors, understand and practice CSR differently to the multinational companies which have dominated extant research. The study found that CSR meaning and practice in this large, but little researched, group of companies was highly context-based and community focused, in marked contrast to the strategies and practices of larger resources companies operating in developing nations. Importantly, the study also revealed striking contradictions and ambiguities between participants' CSR actions and accountability and their assumed SLO. Highlights: Addresses a gap in research into CSR meaning and practice in junior and mid-tier resources companies. CSR was highly localised and community-focused, and moderated by company size and local conditions. CSR meaning and practice was also selective, ambiguous and contradictory. Social licence to operate was assumed on the basis of anecdotal evidence and lack of opposition.